2018
DOI: 10.21834/e-bpj.v3i7.1273
|View full text |Cite
|
Sign up to set email alerts
|

HIV Knowledge, Attitude, and Perception Among University Students

Abstract: Young people aged between 13 to 29 were contributed to the total of 34% of the cumulative infection Human Immunodeficiency Virus (HIV) in Malaysia. The purpose of this study is to determine the level of knowledge, attitude, and perception among students in the University. Research design is cross-sectional. Questionnaire were distributed to 372 respondents. Therefore, 52.4 percent students had a good knowledge. There was positive weak correlation between KA (r =0.23) and KP (r=0.19) with significance (p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…A lack of knowledge can create a negative impact on PLWH and encourage stigmatization and discrimination [7]. In a study in Malaysia, a majority of the students showed a positive attitude towards PLWH, as shown by the results in our study [13]. A study conducted in Croatia, indicated negative attitude towards HIV patients [10].…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…A lack of knowledge can create a negative impact on PLWH and encourage stigmatization and discrimination [7]. In a study in Malaysia, a majority of the students showed a positive attitude towards PLWH, as shown by the results in our study [13]. A study conducted in Croatia, indicated negative attitude towards HIV patients [10].…”
Section: Discussionsupporting
confidence: 63%
“…However, majority of the students involved in the study in India were aware that HIV couldn't be spread through a mosquito bite [18]. At the University in Malaysia, 50.5% of the students believe that healthy people at first glance could be infected with HIV [13]. Moreover, in our survey all students thought that people with HIV can be asymptomatic.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations